Mid-Esophagus Columnar Metaplasia: What Is the Biopathogenic Pathway?. (May 2017) - Rolim, Inês; Rodrigues, Rita Vale; Bettencourt, António; Barros, Rita; Camilo, Vânia; Dias Pereira, António; Almeida, Raquel; Chaves, Paula
We report a case of metaplastic columnar epithelium in the mid-esophagus in a patient with history of caustic ingestion. A cardiac-type gastric phenotype, with early signs of intestinalization, was confirmed by immunohistochemistry studies (MUC5AC, MUC6, SOX2, and CDX2). Nonmetaplastic mucosa had histologic evidence of gastroesophageal reflux. In this case, esophageal reepithelization seems to have been modulated by acidic gastroesophageal reflux, which might activate transcription factors leading to phenotypic reprogramming of the regenerative epithelium. Most interestingly, it is a clinical example showcasing the origin of columnar metaplasia from stem cells located within the esophageal epithelium.